IN-SILICO STUDY OF HERBAL COMPOUNDS (BAICALIN, CURCUMIN AND DRONABINOL) AS NOVEL MAO INHIBITORS FOR PARKINSON’S DISEASE TREATMENT: Life Science-Bioinformatics - SINGH, RAKSHA; CHATURVEDI, NAVNEET; KUMAR SINGH, VINAY (International Journal of Life Science and Pharma Research, 2012)
Parkinson disease (PD) is the second most common neurodegenerative disorder. MAO A and MAO B have important functions in the metabolism of neuroactive and vasoactive amines in the central nervous system. Monoamine oxidase inhibitors may limit the rate of dyskinesia relative to levodopa, the standard therapy for motor control of PD. The MAOs site represents a central target for therapeutics of Parkinson’s disease and major depressive disorder. Monoamine Oxidase (MAOs) isoforms have amine oxidase domain (IPR001613, IPR002937), we have taken the functional signature part to study their homologues in human genome and successfully hunted 14 isoforms related to this family. Templates were selected with 99% sequence identity for both Mao A and Mao B isoforms. 3D structure of MAO A and MAO B were generated, evaluated and submitted to PMDB database and are available with PMDBID; PM0077964, PM0077935 respectively. Some novel herbal bioactive compounds (Baicalin, Curcumin and Dronabinol) have been reported to be useful in neurodegerative disorders, depression and have antioxidative property. Docking was successfully performed for MAO A and MAO B proteins with Baicalin, Curcumin and Dronabinol bioactive compounds and active site coordination was found to be similar as the template residues involved in binding with experimentally used inhibitors. The residues which are involved in the hydrophobic, cation-pi, pi-pi interaction and hydrogen bonding etc. also representing the similarity with the predicted active sites-1 by using Q-site finder with major interacting surface area. Among these three compounds, most effective compound was found to be Dronabinol as showing minimum Inhibition Constant, Ki and lowest free energy of binding for both models. This knowledge may be important for the development of novel drugs for the treatment of Parkinson disease and other neurodegenrative disorders